The Association Between Onset of Staphylococcal Non-menstrual Toxic Shock Syndrome With Inducibility of Toxic Shock Syndrome Toxin-1 Production - Taki, Yusuke; Watanabe, Shinya; Sato’o, Yusuke; Tan, Xin-Ee; Ono, Hisaya K.; Kiga, Kotaro; Aiba, Yoshifumi; Sasahara, Teppei; Azam, Aa Haeruman; Thitiananpakorn, Kanate; Veeranarayanan, Srivani; Li, Feng-Yu; et al. (Frontiers in Microbiology, 2022)
Non-menstrual toxic shock syndrome (non-mTSS) is a life-threatening disease caused by Staphylococcus aureus strains producing superantigens such as toxic shock syndrome toxin-1 (TSST-1). However, little is known about why the TSS cases are rare, although S. aureus strains frequently carry tst gene which encodes TSST-1. To answer this question, the amount of TSST-1 produced by 541 clinical isolates was measured in both the presence and absence of serum supplementation to growth media. Then, a set of S. aureus strains with similar genetic backgrounds isolated from patients presenting with non-mTSS and those with clinical manifestations other than non-mTSS was compared for their TSST-1 inducibility by human serum, and their whole genome sequences were determined. Subsequently, the association of mutations identified in the tst promoter of non-mTSS strains with TSST-1 inducibility by human serum was evaluated by constructing promoter replacement mutants and green fluorescent protein (GFP) reporter recombinants. Results showed that thirty-nine out of 541 clinical isolates (7.2%), including strains isolated from non-mTSS patients, had enhanced production of TSST-1 in the presence of serum. TSST-1 inducibility by human serum was more clearly seen in non-mTSS strains of clonal complex (CC)-5. Moreover, the whole genome sequence analysis identified a set of sequence variations at a putative SarA-binding site of the tst promoter. This sequence variation was proven to be partially responsible for the induction of TSST-1 production by human serum. We conclude that the onset of staphylococcal toxic shock syndrome caused by TSST-1-producing CC-5 strains seem at least partially initiated by serum induction of TSST-1, which is regulated by the mutation of putative SarA-binding site at the tst promoter.